2011
DOI: 10.4319/lo.2011.56.2.0716
|View full text |Cite
|
Sign up to set email alerts
|

Influence of iron on fatty acid and sterol composition of marine phytoplankton and copepod consumers

Abstract: We conducted laboratory experiments to determine the influence of iron on the fatty acid (FA) and sterol composition of the diatom Thalassiosira oceanica, the cryptophyte Rhodomonas salina, the prymnesiophyte Isochrysis galbana, and the copepod Acartia tonsa that fed on these algae. Algal cells were cultured with no added Fe or with Fe added at 100 nmol L 21 . Fe-deficient culture medium resulted in lower growth rates, cell volumes, and photosynthetic efficiencies for all algal species. The total mass of FA pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Addition of 50% lipid μ-caps thus increased the ω3-HUFA content ca. 10-fold, from less than 1% to over 10%., which is even higher than found for most ω3-HUFA rich diatom cultures [46,47]. …”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Addition of 50% lipid μ-caps thus increased the ω3-HUFA content ca. 10-fold, from less than 1% to over 10%., which is even higher than found for most ω3-HUFA rich diatom cultures [46,47]. …”
Section: Resultsmentioning
confidence: 63%
“…By contrast, our study suggests that in up-welling systems such limitation of egg production may play a minor role, since the seston is generally rich in ω3-HUFA, especially EPA and DHA. Due to the sustained input of new nutrients into the euphotic zone that is characteristic of upwelling areas, nutrient saturated conditions of algae prevail, yielding algae that are nutritionally superior to those which are nutrient limited [46,47,48]. In addition, upwelling conditions favor the occurrence of diatoms [49,50], which are specifically rich in ω3-HUFA such as EPA [46,47].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage recoveries of arachidonic acid (20:4(n-6)) after incubation for one 234 hour both at 40 °C and 70 °C were in the range of the RSD. Other authors also reported 235 saponification of lipid extracts at 100 °C without noticeable effect on poly-unsaturated FA 236 quantification (Chen et al, 2011;Goutx et al, 2007). 237 2.6.2.…”
Section: Bulk Parameters: Bsio 2 Poc and Prokaryotic Concentrationsmentioning
confidence: 95%
“…phytoplankton have been identified in different phyla (Fabris et al, 2014;Villanueva et al, 2014;Volkman, 2016). It has been observed that sterol contents (per carbon contents or percentage of total sterols) in phytoplankton changed with temperatures (Vé ron et al, 1996;Piepho et al, 2012;Ding et al, 2019), pCO2 (Gordillo et al, 1998;Riebesell et al, 2000), nutrient availability (Piepho et al, 2010;Gordillo et al, 1998;Chen et al, 2011), and UV-C radiation (Ahmed and Schenk, 2017).…”
Section: Introductionmentioning
confidence: 99%